MEANS OF INDONESIAN MARITIME DEFENSE STRATEGY IN SEA CONTROL ON THE INDONESIAN STRATEGIC STRAITS TO SUPPORT TOTAL DEFENSE AND SECURITY SYSTEM - Amarulla Octavian; Rayindra Asmara; Abdiyan Syaiful Hidayat (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
Indonesia is a country with a water area of 6.4 million km2 or about 2/3 of its territory is the sea. Geographically, Indonesia's position is very strategic because of an international shipping route on it as well as a crossing point between the continents of Asia and Australia and the Pacific and Indian oceans. This configuration of the Indonesian sea area requires strict control to meet all types of demand at all Archipelagic Sea Lanes’ choke points. Therefore, this study was conducted to answer what kind of strategy that needed in controlling the sea at Indonesia's four strategic choke points to support the Total Defense System. This study used a qualitative method with an exploratory approach because the researchers explored deeper and analyzed the objectives, resources, and methods of controlling the sea at four strategic points in Indonesia. The theory of strategy researchers used to discuss problem formulation was assisted by NVivo 12 tools in processing data and Soft System Methodology (SSM) to analyze research data. The results of the research prove that the resources used to achieve Indonesia's maritime defense in controlling the sea at Indonesia's four strategic choke points are the empowerment of power, inter-agency cooperation, and regulation-making in determining maritime defense strategies.